Analisa Pemasaran Digital Terhadap Tingkat Penjualan Jam Tangan di Indonesia - Lady Lady; Chris Levenise (Universitas Internasional Batam, 2021)
This study aims to determine digital marketing on the level of watch sales in Indonesia. The independent variables used in this study are Information Quality, Information Credibility, Website Quality, Innovativeness, Social Support, Attitude Towards e-WOM, e-WOM Engagement, and Purchase Intention as the dependent variable. The number of samples using the 1:10 technique to find out how many samples. 242 data were distributed via google form, then analyzed using SmartPLS version 3.3. The results of this study indicate that there is a significant influence between Information Credibility, Website Quality, Social Support, e-WOM Attitude Towards on e-WOM Engagement and e-WOM Engagement on Purchase Intention. Meanwhile, Information Quality, Innovativeness variables have no significant effect on e-WOM Engagement and e-WOM Attitude Towards have no significant effect on Purchase Intention.